Focal crisis originating from movement in a hyperglycemic nonketotic patient - J. Adamo Jr.; F. Forti (Arquivos de Neuro-Psiquiatria)
Case report of a long term diabetic patient with partial motor crises originating from passive movement of the right arm. This is a rare type of crisis when compared to spontaneous partial crisis in diabetic patients. Partial crises are often the initial manifestation of diabetes mellitus (about 19% of the cases reported). As in those cases registered in the literature, crisis control in this case was obtained by normalization of glycose serum levels. Possible mechanisms involved in the pathogenesis are discussed.